RELATIONSHIP BETWEEN KNOWLEDGE OF INCLUSIVE EDUCATION AND TEACHERS' PERCEPTIONS OF STUDENTS WITH SPECIAL NEEDS - Sulistiyaningsih, Ernawati; Sari, Yessy Yanita; Nuriadin, Ishaq (Faculty of Administrative Science, Universitas Brawijaya, 2025)
The present study aimed to investigate the correlation between Inclusion Education Knowledge and teacher perceptions of students with special needs towards teacher attitudes in Duren Sawit Public Elementary School of East Jakarta. A quantitative study was conducted with 173 respondents from various public elementary school work units in Duren Sawit. Participants completed a questionnaire distributed via a Google Form link. The questionnaire included multiple-choice questions related to teacher knowledge and statements using the Likert scale to assess Teacher Perception and Teacher Attitude variables. The results of hypothesis testing revealed that the significance value of the Teacher Knowledge variable on the Teacher Attitude variable was 0.088 and significant at α 5% level. This suggests no significant correlation between Teacher Knowledge and Teacher Attitude toward providing educational services to students with special needs and other students in the classroom. However, there was a significant correlation between the Teacher Perception variable on Teacher Attitude and thus can be accepted as the result of the study, with a value of 0.000 and significance at α 5%. From the research findings above, there is a simultaneous correlation between variables of Teacher Knowledge and Teacher Perception toward Teacher Attitude and can be accepted as the research result, with a value of 0.000 and significance at α 5%. The percentage of the correlation explained by teacher knowledge on inclusive education and teacher perception of teacher attitude is 0.338 or 33.8%, while the other factors likely to be influence teacher motivation.